(untitled) (American International Journal of Education and Linguistics Research, 2019)
The Study Examined Qualitative Aspect Of “O” Level West African Secondary School Certificate Practical Chemistry Syllabus And Identified Reaction Of Metals With Water As One Of The Concepts That Chemistry Teachers Avoid To Teach Due To Either Unavailability Of Chemical Regents Or Lack Of Teachers’ Competence To Handle The Topic. The Study Therefore Examined The Effectiveness Of Process Oriented Guided Inquiry Leaving (POGIL) Strategy On Students’ Performance In Chemistry In Secondary Schools In Ondo State, Nigeria. A Pretest, Posttest Control Group Design Was Adopted With POGIL Being the treatment and lecture method as the control group. A total of 60 Senior Secondary School chemistry students (SSS 3) were randomly selected from Akoko South West Local Government Area of Ondo State Nigeria to constitute the study sample. Two intact classes comprising 33 students for POGIL group and 27 students for the lecture method group were taught separately in their respective schools. A 1 item instrument tagged Practical Chemistry Achievement Test (CAAT) with reliability co-efficient of r=0.78, p<0.05 was used to collect data. The results showed that POGIL was more effective (=12.63) than lecture method (=10.84), t=2.97, p<0.05. The study concluded that POGIL strategy is an effective method of teaching practical chemistry concepts in general and the qualitative aspect of practical chemistry in particular.